2016
DOI: 10.2196/jmir.5534
|View full text |Cite
|
Sign up to set email alerts
|

Telemedical Education: Training Digital Natives in Telemedicine

Abstract: Telemedicine plays an important role in the delivery of medical care, and will become increasingly prominent going forward. Current medical students are among the first generation of “digital natives” who are well versed in the incorporation of technology into social interaction. These students are well positioned to apply advances in communications to patient care. Even so, providers require training to effectively leverage these opportunities. Therefore, we recommend introducing telemedicine training into me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 8 publications
1
79
0
1
Order By: Relevance
“…Students must have opportunities to directly compare and contrast traditional medicine practices with those of telemedicine. Doing so will permit them to recognize when it is safe and appropriate to use a telemedicine approach and to acquire and ultimately adopt best practices (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students must have opportunities to directly compare and contrast traditional medicine practices with those of telemedicine. Doing so will permit them to recognize when it is safe and appropriate to use a telemedicine approach and to acquire and ultimately adopt best practices (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, the comfort factor alone does not guarantee that this cohort will be able to perform high quality care via telemedicine approaches. While these students do have an advantage in their familiarity and comfort with technology, their skills in using the technology as an alternative to face-to-face interaction must be developed through structured training (10). Examples of core requirements identified previously include digital literacy, basic health information technology skills, and appropriate security and privacy training (11).…”
Section: Changing the Landscape Of Healthcare With Digital Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies have suggested that digital health worker training is incorporated into the standardized medical training curriculum [5,10,47], others advocated for training at the workplace (i.e. in-service training) [10].…”
Section: Design Structure Of the Standard Dh Worker Curriculum For Thmentioning
confidence: 99%
“…In Table 4 and Table 5 respectively, are summaries for structures of the standard DH pre-service and in-service curricula for the African region. Although studies have suggested that digital health worker training is incorporated into the standardized medical training curriculum [4,10,50], others advocated for training at the workplace (i.e. in-service training) [10].…”
Section: Proposed Structure Of the Standard Dh Worker Curriculum For mentioning
confidence: 99%